An Empirical Investigation to Understand the Impact of Social Media on Consumer Behavior Using Multiple Regression Analysis - P, guru.; V, rishnapriya; V, 3subhamathi. (International Journal of Engineering and Technology, 2018)
Technology gives consumer the platform to investigate products to label them and criticize them in equal measure, and more. Therefore at present many companies have pages on social networks to share and create visibility about products, held by the feedback of consumers about products and tend to relate more to a company after going through various comments and reviews. Most studies show that the internet and social media usage is changing consumer behavioral pattern and also witnessed in developing countries such as India. In recent years, the online environment is viewed by users from a commercial perspective. Its development and the emergence of online stores have turned users into prospective consumers. Also the most important role of social media has changed the way of how consumers and marketers communicate with each other. Informational society influence affects the consumer decision processes and product evaluations. Social media provides a new channel to acquire product information through peer communication. This research will offer an overview on how the consumers use social media in the stages of decision making process and the psychographic variables that influence their behavior. The implication of these findings suggests about the segment in which, the insurance business in India should focus their market research and marketing strategy.Â